Brewing Terminologies Used by Baristas: Contextualized Instructional Material for Technical, Vocational, and Livelihood Students - Pearlene L. Serviano; John Brian P. Esporas; Joy M. Gelantaga-an; Garneth T. Granada; John Gil Lorenzo D. Ricablanca; Ruel T. Bonganciso (Journal of English as A Foreign Language Teaching and Research, 2024)
As coffee industries grow, the demand for good coffee is not simply enough nowadays. As a result, lexicons related to coffee, coffee beans, flavors, tools and equipment, and its processes are ever growing; hence, it can be considered “alive”. This study aims to gather coffee-related lexicons to create contextualized learning materials for Technical Vocational Learning (TVL) students, addressing the shortage of resources needed to enhance their coffee brewing skills. This study utilized two methods of acquiring data: 17 baristas from selected traditional coffee shops in the Philippines as participants of the study and books, articles and websites as the corpus of the study. Qualitative content analysis was used to identify common terminologies and their contextualized conceptual and operational definitions, as well as unique lexicons used by local baristas, which were then categorized into flavors, tools and equipment, and processes. After collecting 76 terminologies, it underwent thematic analysis and was categorized according to themes, such as coffee beans, flavors, serving sizes, tools and equipment, and processes. By incorporating these lexicons in the context of education, it will enhance students’ knowledge about coffee culture, industry practices and professional terminology, all of which are necessary for effective communication. This study contributes to the continuous evolution of language in the coffee industry by documenting and analyzing the diverse terminologies used.